Please no more PID tuning rules - Oliveira, Paulo de Moura (2002)
Despite the large number of existent design and tunig techniques, adequate PID controller tuning by plant operations is still not accomplished in many process control loops. The particle swarm optimisation algorithms is proposed as an alternative technique to design and tune PID controllers for linear single-input single-output systems. This evolutionary approach is illustrated by a simulation example, in which the PID is used to control a set of models that represents a wide variety of process dynamics, regarded as benchmak problems for the evaluation of commercial devices involving PID control.